SISTEM PEMASARAN LADA HITAM DI KABUPATEN LAMPUNG BARAT PROVINSI LAMPUNG - M Pandu Pradyatama; Ali Ibrahim Hasyim; Suriaty Situmorang (Lampung University, 2019)
This research aims to analyze the efficiency of black pepper marketing system in West Lampung Regency of Lampung Province. The research was conducted purposively at Fajar Bulan and Mutar Alam Village of Way Tenong Subdistrict, Sukajadi and Rigis Jaya Village of Air Hitam Subdistrict in October-December 2017. Farmer respondents and marketing agent respondents were taken by tracing marketing networks. Data analysis included analysis of marketing system efficiency was conducted by employing SCP method. The results showed that the marketing system of black pepper in West Lampung Regency weren’t efficient based on: the market structure was an imperfect competition, the market conduct showed pepper price determination by pepper buyers, but there was still negotiation system. There were two payment systems that were cash and credit system. The analysis of market performance showed that there were three marketing channelsin which marketing margin were relatively high, Ratio Profit Margin not spread evenly, and the elasticity of price transmission (Et) was less than one, although producer share (PS) value was high (above 80 percent). Key words : black pepper, efficiency, marketing system, SCP method